Perancangan Keselamatan dan Kesehatan Kerja dengan metode HIRARC di PT X - Poernomo, Yohanes Robby Surya; Sutapa, I Nyoman (Jurnal Titra, 2019)
The design of HIRARC is used to analyze Occupational Safety and Health at PT X. The stages used in this design by identifying hazards in the Production Department, hazard identification is carried out by field observations and interviews with operators. The next stage with risk assessment, from the results of the risk assessment the highest potential hazard values are the dangers of dust, noise hazards, and fire hazards with significant values I and II which can be classified in the medium and high risk. Control of these hazards is the making of sanctions regulations on workers who do not use personal protective equipment, make a schedule for checking machines, socialize to workers.